2016
DOI: 10.3892/or.2016.4948
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the miRNA expression by TEL/AML1, BCR/ABL, MLL/AF4 and TCF3/PBX1 oncoproteins in acute lymphoblastic leukemia (Review)

Abstract: MicroRNAs (miRNAs) are a class of small endogenous non-coding RNAs that play important regulatory roles by targeting mRNAs for cleavage or translational repression. miRNAs act in diverse biological processes including development, cell growth, apoptosis, and hematopoiesis. The miRNA expression is associated with specific cytogenetic changes and can also be used to discriminate between the different subtypes of leukemia in acute lymphoblastic leukemia with common translocations, it is shown that the miRNAs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…26 Common fusion genes in ALL patients include the BCR/ABL fusion gene and the TEL/AML1 (ETV6 /RUNX1) fusion gene with an incidence of ~6%-35%, and the latter is considered to be a fusion genes associated with good prognosis. 27 Herein, we also found that the expression of PKM2 in ALL patients with BCR/ABL gene fusion was higher than that in other patients without gene fusion, while there was no statistically significant difference in the expression level of PKM2 between AML patients with PML-RARA gene fusion or ALL patients with TEL/AML1 gene fusion. Studies have confirmed that BCR-ABL fusion gene encodes BCR-ABL fusion protein and drives tumor transformation of hematopoietic stem cells, which can stimulate the PI3K/Akt/ mTOR signal transduction and lead to impaired autophagy of leukemia cells.…”
supporting
confidence: 48%
“…26 Common fusion genes in ALL patients include the BCR/ABL fusion gene and the TEL/AML1 (ETV6 /RUNX1) fusion gene with an incidence of ~6%-35%, and the latter is considered to be a fusion genes associated with good prognosis. 27 Herein, we also found that the expression of PKM2 in ALL patients with BCR/ABL gene fusion was higher than that in other patients without gene fusion, while there was no statistically significant difference in the expression level of PKM2 between AML patients with PML-RARA gene fusion or ALL patients with TEL/AML1 gene fusion. Studies have confirmed that BCR-ABL fusion gene encodes BCR-ABL fusion protein and drives tumor transformation of hematopoietic stem cells, which can stimulate the PI3K/Akt/ mTOR signal transduction and lead to impaired autophagy of leukemia cells.…”
supporting
confidence: 48%
“…15 MiRNAs may be especially important in regulating the expression of TFs such as MYB that has distinct biological effects in normal hematopoiesis and in leukemic cells based on its expression levels. 15,16 Regulation of MYB expression through miRNAs has been reported previously. 1720 Levels of MYB expression may be differentially controlled by multiple miRNAs and, conversely, MYB could control the expression of different miRNAs 9,1721 to execute lineage-specific developmental choices at critical junctions during hematopoiesis.…”
Section: Introductionmentioning
confidence: 79%
“…47 On the other hand, silencing MYB alone does not abolish expression of the miR-17-92 cluster, suggesting that other transcription factors also regulate the expression of the miR-17-92 cluster in BCR-ABL1 -transformed cells. 16 Compared to control cells, MYB -silenced BV173 cells exhibit a marked inhibition of cell growth which is due to cell-cycle arrest and induction of apoptosis. 48 Thus, we asked whether restoring expression of the miR-17-92 cluster would rescue the impaired growth of MYB -silenced BV173 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR-708 upregulation was associated with a good prognosis, as lower relapse risk, low WBC count, and better overall survival were detected in ALL cases; on the contrary, miR-708 downregulation was revealed in poor prognosis subtypes as T-ALL and cases with MLL gene rearrangement [122,139]. Finally, in ALL with TCF3-PBX1 fusion, the deregulation of several miRNAs was also revealed (Table 1) [123,127].…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 98%